ANALISIS RE-MAPPING PADA MESIN SEPEDA MOTOR MATIC 4 TAK 110 CC MENGGUNAKAN KNALPOT CUSTOM TERHADAP PERFORMA - Ayu Oktaviana Savitri; Sena Mahendra; Fahmy Zuhda Bahtiar; Fathur Rahman (Journal of Vocational Education and Automotive Technology, 2025)
Analysis of Re-mapping on a 110 CC 4 Stroke Automatic Motorcycle Engine Using a Custom Exhaust on Performance. Semarang. Mechanical Engineering Vocational Education. Faculty of Science and Technology. Ivet University Semarang. This research uses experimental methods and a quantitative approach. A descriptive data analysis technique that compares the effect of using a standard ECU and remapping 3 times with 2 types of exhaust on the performance of the Beat 110 cc motorbike. The research results show that (1) The highest torque when using a custom exhaust with a fuel flow of 2%, an ignition angle of 1º, a 9,000 rpm limiter produces 9.89 at 4,000 rpm, the torque increases by 2%; (2) The highest power when using a custom material discharge of 2%, 1º ignition angle, 9,000 rpm limiter produces 5.75 at 8,500 rpm, power increases by 8%; (3) The best specific fuel consumption (SFC) when using a custom exhaust and standard ECU reaches an increase of 68% at rpm 9,000; (4) In exhaust gas emissions, CO levels decreased very drastically by 2% in standard ECUs and using custom exhausts, the best CO2 in standard ECUs and custom exhausts with an increase of 18%, the best HC produced in remapping ECUs with custom exhausts experienced an increase of 25%. %, O2 has increased by 4% on ECU remapping with custom exhaust.